Prevalence and Population at Risk for Noise Induced Hearing Loss (NIHL) in Adolescent Students - Yusni, Yusni; Ikbal, Ikbal; Meutia, Firdalena (Folia Medica Indonesiana, 2021)
Noise-Induced Hearing Loss (NIHL) is a global health problem, often underestimated, and leads to permanent hearing loss. The prevalence of NIHL in adolescents has increased in line with the increasing use of cell phones. This study aimed to determine the prevalence of NIHL and analyze the population at risk (age, gender, and school) in adolescent students. The study design was a cross-sectional study. A total of 510 students consisting of female, n=288 and male, n=222; junior high school, n=203 and senior high school, n=307 were used as research subjects. This study was conducted on August-October 2015 at Darul Ihsan School, Banda Aceh, Indonesia. An audiometry examination was performed to determine the diagnosis of NIHL. Data analysis was using descriptive analysis and independent sample t-test(p<0.05). The results of this study were the prevalence of NIHL in adolescents aged 11-20 years was 18.88%. The highest percentage of NIHL was at the age of 15 years (34.57%). The number of NIHL was significantly higher (p=0.000*) in males (24.32%) compared to females (9.37%). The prevalence of NIHL was significantly higher (p=0.00*) in senior high school children (26.11%) compared to that in junior high school children (9.12%). In conclusion, the highest prevalence of NIHL was at the age of 15 years. NIHL was more common in male than in female students. NIHL was higher in high school students compared to junior high school students. The NIHL was related to age, gender, and school level.